Liberation Theology and Gender (Asghar Ali Engineer's Thoughts) - Maulidiy, Fahmidiya Khilda; Masrohatin, Siti; Fathiyaturrahmah, Fathiyaturrahmah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Asghar Ali Engineer (1939-2013) was a theologian and feminist from India. Born into an elite religious environment, he then experienced dirty exploitation in the name of religion which made him study the nature of religious law. He collaborated between Islamic literature and Western literature to discover the essence of Sharia. This article will discuss his popular thoughts on liberation theology and gender and Asghar Ali's efforts in reinterpreting the Koran. The research method used in this study is qualitative research, a type of library research. The research data source uses books written by Asghar Ali and several studies that are relevant to the research focus. Based on the research results, in interpreting the Qur'an Asghar Ali used three methods. One way is to differentiate the normative and contextual aspects of a verse to understand the historical aspects when the Qur'an. Another side discussed by Asghar Ali is gender, for him, gender equality and gender justice are closely related. The realization of justice and gender equality is realized by the absence of discrimination between men and women, as well as the opportunity to participate in all aspects of life. This cannot be separated from the situation in India where he lives, where there is inequality and injustice between men and women. The research results concluded that it is necessary to reinterpret the interpretation of the Qur'an so that the theological views regarding the Qur'an Salihun Li Kulli Zaman Wa Makan can still be applied in life while still prioritizing human values.